Peningkatan Kualitas Santri TPQ Darul Falah Mojo dengan Pengadaan Fasilitas serta Pelatihan Soft dan Hard Skill - Santoso, Agus Dwi; Shafira, Alya Jasmine; Mukharomah, Hanifah Putri Nur; Putra, Jonathan Rizki Eka; Romadoni, Selfi Amalia (Fakultas Tarbiyah IAIN Kediri, 2024)
Taman Pendidikan al-Qur'an (TPQ) is an educational institution whose focus of learning is reading and writing the Qur'an as well as a basic understanding of Aqidah, morals and shari'a on santri or students. TPQ Darul Falah students located in Gedangan Mojo hamlet have very high enthusiasm in studying, but are constrained by limited teaching staff, lack of parental awareness in supporting children to learn religious knowledge and pay tuition fees and lack of adequate facilities to support student learning. The KKN group tries to empower TPQ Darul Falah to become a more comfortable place to learn and foster interest and motivation in students in the learning process. In this research, the method used is Participation Action Research (PAR). The KKN 07 group in Mojo village collaborated with YBM PLN in helping to procure facilities at TPQ Darul Falah. The facilities provided to TPQ Darul Falah to support the students' human resources are as follows: Neon box, 4 blackboards, 4 tables, books, Qur'an, iqra', stationery, hijaiyah posters and so on. In addition to providing physical facilities, the KKN group also provides training in both soft and hard skills based on religion to the students. So that the students are able to develop their potential and be able to apply it in their daily lives.